2000
DOI: 10.1093/molehr/6.10.943
|View full text |Cite
|
Sign up to set email alerts
|

Localization of E-cadherin in villous, extravillous and vascular trophoblasts during intrauterine, ectopic and molar pregnancy

Abstract: Previous reports have described down-regulation of E-cadherin in trophoblasts differentiating to an invasive phenotype. This study shows the localization of E-cadherin in a prospective design with stereological sampling of fetal and maternal first, second and third trimester tissue. E-cadherin was observed in villous cytotrophoblasts, and in non-proliferating, intermediate trophoblasts (IT) within cell columns and islands in intrauterine, ectopic and partial molar placentas. Highly proliferating IT with cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 34 publications
6
51
0
Order By: Relevance
“…We infected the guinea pig colorectal adenocarcinoma cell line GP-16 with an InlA deletion mutant of L. monocytogenes and found a 2-log-unit reduction in invasion (data not shown). We subsequently tested whether InlA or InlB facilitated invasion of trophoblasts, in particular because trophoblasts express E-cadherin and c-Met-tyrosine kinase (12,21). Infection of BeWo cells with an InlA deletion mutant of L. monocytogenes led to a 2-log-unit reduction in invasion in comparison to wild type infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We infected the guinea pig colorectal adenocarcinoma cell line GP-16 with an InlA deletion mutant of L. monocytogenes and found a 2-log-unit reduction in invasion (data not shown). We subsequently tested whether InlA or InlB facilitated invasion of trophoblasts, in particular because trophoblasts express E-cadherin and c-Met-tyrosine kinase (12,21). Infection of BeWo cells with an InlA deletion mutant of L. monocytogenes led to a 2-log-unit reduction in invasion in comparison to wild type infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 Ecadherin is present in villous cytotrophoblasts and is reduced in the distal regions of the EVT cell columns and in migrating and invading EVT within the decidua in first and second trimester placental tissues. 65 Floridon et al, 66 reported a transient down regulation of E-cadherin expression in migratory and invasive EVT that was restored when trophoblasts aggregated in the decidua to form giant cells, and in the vessel wall after completion of trophoblast migration and invasion. In vitro evidence demonstrated that knock-down of E-cadherin significantly increased invasiveness of the EVT cell line JEG-3 56 and of isolated second trimester trophoblast cells.…”
Section: Downstream Gene Targets/cell-adhesion Molecules In Emtmentioning
confidence: 99%
“…In these disorders as well as in gestational trophoblastic diseases, like hyadatiform mole, Cdh1 expression is frequently altered in comparison to normal pregnancies. Both an increase in Cdh1 expression and an aberrant down-regulation have been documented in different studies (Zhou et al, 1997;Floridon et al, 2000;Xue et al, 2003;Brown et al, 2005;Batistatou et al, 2007;Blechschmidt et al, 2007). However, the role of cadherin-mediated adhesion for placenta formation and tissue homeostasis and in the described disorders remains elusive.…”
Section: Cdh2/cdh2mentioning
confidence: 98%
“…Subsequently, the protein is lost during syncytiotrophoblast differentiation (Shih Ie et al, 2002). Altered Cdh1 expression is likely the cause for certain complications during pregnancy, such as pre-eclampsia or some spontaneous abortions, and can be detected in gestational trophoblastic syndromes (Zhou et al, 1997;Floridon et al, 2000;Xue et al, 2003;Batistatou et al, 2007). In pre-eclampsia, an incomplete invasion of the extravillus trophoblast into the uterine endometrium was identified, which correlates with aberrant Cdh1 expression (Zhou et al, 1997;Brown et al, 2005).…”
Section: Developmental Dynamicsmentioning
confidence: 99%